Physiology, evolution and single cell gene expression : an experimental approach using a microfluidics technique (2017)
"Interest in studies about variability in gene expression has been increasing due to its applications in pharmaceutical, medical and biological sciences. Genetically identical cells can have different phenotypes even when they are growing in the same environmental conditions; this is just one of many examples of the consequences of stochasticity in the chemical reactions at a molecular level. In our work we try to find insights on the sources of physiology and gene expression variability and their interaction with the environment, such as the case of nutrient limitation." -- Tomado del Formato de Documento de Grado.